Boron Nanoparticles for Room‐Temperature Hydrogen Generation from Water. Issue 12 (9th April 2016) - Rohani, Parham; Kim, Seongbeom; Swihart, Mark T.
Abstract : Boron nanoparticles (BNPs) are of great interest for applications such as neutron capture therapy of cancer cells, hydrogen generation from water, and high energy density fuels. Boron is particularly interesting for chemical water splitting, because of its high gravimetric hydrogen generation potential of 277 g H2 per kg B. However, only a few studies of water splitting by reaction with boron are available, and those have used high temperature steam with external heating. Room‐temperature boron hydrolysis is of great interest from both scientific and practical perspectives. The studies presented here demonstrate that high purity amorphous BNPs can be oxidized by water to produce H2 at room temperature, without external energy input, in the presence of catalytic quantities of an alkali metal or alkali metal hydride. The BNPs are produced in a single step gas phase process via CO2 laser‐induced pyrolysis of mixtures of B2 H6 and SF6 . The BNPs are spherical with a primary particle diameter of 10–15 nm, narrow size distribution, and specific surface area exceeding 250 m 2 g −1 . This first demonstration of room‐temperature chemical splitting of liquid water using boron opens up exciting new possibilities for on‐demand hydrogen generation at high gravimetric capacity. Abstract : The reaction of water with inorganic solids provides a convenient means of on‐demand hydrogen generation. Boron has the highest gravimetric hydrogen generation potential among inorganic materials, but is water reactive only at high temperatures. Results presented here show that amorphous boron nanoparticles generate hydrogen from liquid water at room temperature in the presence of catalytic quantities of NaH or alkali metals.